Economic Empowerment of Coastal Women: The Effect of Entrepreneurship Education on Self-Efficacy and Financial Literacy Mediation - Yati Yati; Andi Tenri Ampa; Andi Annisa Sulolipu; Agussalim Agussalim (Economics Education Department Universitas Negeri Semarang, 2025)
This study aims to analyze the effect of entrepreneurship education on the economic empowerment of coastal women with self-efficacy and financial literacy as mediating variables in Makassar City. Quantitative research was used involving 100 coastal women respondents selected through purposive sampling. Data were collected using a structured Likert-scale questionnaire and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results showed that entrepreneurship education has a positive and significant effect on women's economic empowerment. Entrepreneurship education has a positive and significant effect on coastal women's self-efficacy. Entrepreneurship education influences coastal women's financial literacy. Indirectly, coastal women's economic empowerment is positively and significantly influenced by entrepreneurship education through self-efficacy. Entrepreneurship education has a positive, significant effect on the economic empowerment of coastal women in Makassar City by enhancing their financial literacy. Important findings show that self-efficacy and financial literacy can partially and significantly mediate the relationship between entrepreneurship education and coastal women's economic empowerment. This research model emphasizes the importance of entrepreneurship education, not only focusing on knowledge transfer but also on building self-confidence and financial literacy to empower sustainable economic development for coastal women in Makassar City.